2020
DOI: 10.1029/2020jc016223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shoaling Ocean Surface Waves on Wind Stress and Drag Coefficient in Coastal Waters: 2. Tropical Cyclones

Abstract: This study investigates the impacts of shoaling waves on the wind stress and drag coefficient (Cd) in coastal waters during tropical cyclone (TC) landfall. Numerical experiments are conducted using idealized TCs with two intensities, Category 1 and 5, and two translation speeds, 5 and 10 m/s, propagating toward and normal to the shoreline over two bottom slopes, 1:200 and 1:2000. The wave spectra are simulated using the WAVEWATCH III wave model. The unresolved high‐frequency spectral tail is parameterized as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…, field observations (French et al, 2007;Hsu et al, 2017;Jarosz et al, 2007;Potter et al, 2015;Zhao et al, 2015), and numerical simulations (Chen, Ginis, & Hara, 2020;Moon et al, 2004;Reichl et al, 2014) confirmed the saturation and the consequent attenuation of 𝐴𝐴 𝐴𝐴D , although the critical wind speeds 𝐴𝐴 𝐴𝐴10𝑐𝑐 for the saturation were quite different. Holthuijsen et al (2012) found that the 𝐴𝐴 𝐴𝐴10𝑐𝑐 was ∼40 m/s based on the wind profiles measured by GPS drop-sondes.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…, field observations (French et al, 2007;Hsu et al, 2017;Jarosz et al, 2007;Potter et al, 2015;Zhao et al, 2015), and numerical simulations (Chen, Ginis, & Hara, 2020;Moon et al, 2004;Reichl et al, 2014) confirmed the saturation and the consequent attenuation of 𝐴𝐴 𝐴𝐴D , although the critical wind speeds 𝐴𝐴 𝐴𝐴10𝑐𝑐 for the saturation were quite different. Holthuijsen et al (2012) found that the 𝐴𝐴 𝐴𝐴10𝑐𝑐 was ∼40 m/s based on the wind profiles measured by GPS drop-sondes.…”
mentioning
confidence: 74%
“…The long fetch allowed for the development of wind‐wave, which in turn enhanced CD ${C}_{\mathrm{D}}$. Chen, Ginis, and Hara (2020) attributed this enhancement to the shoaling wave effect. Furthermore, the wave age in the right front quadrant was larger than that in the right rear quadrant, which was another factor that affects the wind stress.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations